Investigating lineout performance between the top and bottom four English Premiership rugby union teams in the 2016/17 season - Migdalski, A. H.; Stone, J. A. (International Journal of Performance Analysis in Sport, 2019)
This study investigated lineout performance between the top and bottom four English Premiership rugby union teams during the 2016/17 season. A season long review was conducted analysing all of the top four (n = 1152) and bottom four teams` (n = 1124) lineouts. Findings showed the number of tries scored originating from a lineout play for the top four teams` (1.57 tries per match) was higher in comparison to the bottom four teams` (1.10 tries per match) (p < .05). Lineout success did not change between the top (87%) and bottom (85%) four teams (p > .05). However, the top four teams were more effective in stealing opposition possession at a lineout (17%) compared to the bottom four teams (9%, p < .05). Additionally, top four teams showed a more forwards orientated style of play using binding actions (top = 62%, bottom = 56%, p < .05) and maul formation (top = 55%, bottom = 47%, p < .05). These results suggest coaches should focus on analysis of opposition tactics in lineout play in an aim to develop effective strategies to steal opposition possession at a lineout.